Exploring Managerial Supervision Practices in Tahfidz Programs to Enhance Students’ Memorization Effectiveness - Miftahul Khoiriyah; Baharuddin Baharuddin; Nur Asnawi; M Aqil Fahmi Sanjani; Tri Agung Yoga Prasojo (Universitas Nurul Jadid, 2025)
This study aims to analyze the role of managerial supervision in improving the effectiveness of student memorization in the tahfidz program. This research is rooted in the growing demand for quality tahfidz education that ensures not only the quantity of memorization but also retention and consistency. This study used a qualitative, multi-case study involving selected Islamic educational institutions, with data collected through interviews, observations, and documentation. The data were analyzed using thematic analysis to identify patterns related to supervision practices and memorization outcomes. The findings indicate that integrated managerial supervision significantly improved coordination and consistency in memorization activities. Furthermore, the implementation of a 24-hour supervision system strengthened student discipline and supported the process of continuous memorization and revision. Differentiated supervision based on students' memorization capacity also increased motivation and learning effectiveness by aligning targets with individual abilities. Structured evaluation and continuous feedback mechanisms contributed to better retention and performance. The integration of supervision across academic and residential settings enabled real-time monitoring and timely intervention. This study contributes to the development of educational management theory by integrating the frameworks of supervision, adaptive learning, and quality assurance in tahfidz education.